Cost optimization of thermoelectric materials for power generation: The case for ZT at (almost) any cost. (15th January 2016) - Dames, C.
Graphical abstract: Abstract: We quantify the tradeoff between ZT and materials cost for thermoelectric energy scavengers, considering 31 real materials. It is nearly always practical to aggressively miniaturize the legs until the overall system cost is limited by the heat exchangers and ceramic spreader plates. For thermoelectric materials costing less than C crit . ‴ ∼ 1 /cm 3 (∼100 /kg), the material might as well be free, and even costs as high as ∼10 /cm 3 (∼1000 /kg) may still be acceptable. Thus, the materials goal is maximizing ZT at (almost) any cost.